PHYSICAL AND CHEMICAL CHARACTERIZATION OF EFFLUENT OF SHRIMP AND ITS IMPACTS TO THE ENVIRONMENT - Jeronimo, Carlos Enrique; Balbino, Caio Pio (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706273 Currently, the mangrove regions of the state of Rio Grande do Norte, have suffered greatdevastation caused by the rapid growth of shrimp farming in which it is operated improperlythreatening the ecosystem and the local population. Has become quite a critical situation in termsof water contamination, destruction of native vegetation and reduction of marine species(especially crab). It is true, then, that the degradation of mangroves will result in ecologicalimbalance, with unpredictable consequences. Among the main culprits in the production cycle forthe impacts to the environment, we highlight the effluents generated in step production. Thiseffluent is composed mostly of raw organic decomposition (feed wastes, carcasses of deadanimals, waste fecal etc.) as well as chemical agents such as antibiotics and antioxidants. Aiming toreduce problems caused by improper disposal of effluents of these masses, we intend to studyand adjust treatment processes of physical, chemical and microbiological tests to reduce the impacts of such effluents, as well as adapting the activity to the legal standards of provisionindustrial effluents.